Start-up complexity and the thickness of regional input markets - Dirk Dohse; Andrea Vaona (Kiel Institute for the World Economy (IfW), 2013)
Although there is a large and rapidly growing literature on the determinants of regional variation in new firm formation, relatively little is known about the interrelation between the characteristics of start-up firms and urban structure. It is only recently that scholars of urban economics have suggested a theoretical link between the thickness of regional input markets and the complexity of feasible start-ups. The current paper classifies start-ups in different industry groups according to their complexity and analyzes the impact of regional input market thickness on the frequency of start-ups with different degrees of complexity. We find that thicker input markets do indeed foster more complex start-ups, but that some inputs are more important than others.
Keywords: L26; D22; R12; M13; O31; 330; Entrepreneurship; Start-up complexity; Thick markets; Regional analysis